PENGARUH ANOMALI PASAR TERHADAP RETURN SAHAM PERUSAHAAN FARMASI YANG TERDAFTAR PADA BURSA EFEK INDONESIA PERIODE 2018-2022 - Palullungan, Fisca Fideline; Moh. Athoillah (Contemporary Studies in Economic, Finance and Banking, 2023)
This study aims to determine whether the Week-Four Effect, Rogalski Effect, and The Day of the Week Effect exist and have an impact on the return of shares of pharmaceutical companies listed on the IDX. Ten pharmaceutical businesses listed on the IDX between 2018 and 2022 were a sample of the study. Financial Statements and www.yahoofinance.com provide research data. Descriptive analysis and regression of panel data are used to test hypotheses. The Day of the Week Effect and Week Four Effect factors had a positive and significant impact on the results of the study, while the Rogalski Effect variables did not have a significant impact. This research aligns with the Event Study theory and Signal theory, which will have a good impact on pharmaceutical companies in increasing returns because the information reflected is informative